A Phenomenologycal study on kleptomania behaviour adolescent - Rachim, Annisa Fajrina; Sri Nugroho, Arif Julianto; Semet, Lithianie Fransisca N.B; Azzahra, Nazhifa Fathia; Tasari, Tasari; Almasitoh, Ummu Hany; Febrianty S, Anna; Murjito, Winarno Heru (Universitas Sarjanawiyata Tamansiswa, 2023)
Adolescence is the phase between childhood and adulthood. Teenagers will commit acts of juvenile delinquency when they experience a broken-home and have conﬂicting parents. One of the acts of juvenile delinquency is stealing which has a relationship with impulse control. This study aims to determine the behavior of broken-home adolescents who experience kleptomania disorder and identify the emotions that arise before and after the onset of kleptomaniac behavior. This study uses a phenomenological approach with a semi-structured interview for data collection. Participants in this study were selected through purposive sampling based on predetermined criteria. The data analysis used in this study is the Miles and Huberman interactive analysis model. This study found that participants had a tendency towards kleptomania in childhood due to internal factors. This research is expected to provide objective information about broken-home adolescents who experience kleptomania based on phenomenological studies.